The effects of weight cycling on lifespan in male C57BL/6J mice - List, Edward O. (2012)
OBJECTIVE: With the increasing rates of obesity, many people diet in attempts to lose weight. Since weight loss is seldom maintained in a single effort, weight cycling is a common occurrence. Unfortunately, reports from clinical studies that have attempted to determine the effect of weight cycling on mortality are in disagreement, and to date, no controlled animal study has been performed to assess the impact of weight cycling on longevity. Therefore, our objective was to determine whether weight cycling altered lifespan in mice that experienced repeated weight gain and weight loss throughout their lives. METHODS: Male C57BL/6J mice were placed on one of three lifelong diets: a low fat (LF) diet, a high fat (HF) diet, or a cycled diet in which the mice alternated between 4 weeks on the LF diet and 4 weeks on the HF diet. Body weight, body composition, several blood parameters and lifespan were assessed. RESULTS: Cycling between the HF and LF diet resulted in large fluctuations in body weight and fat mass. These gains and losses corresponded to significant increases and decreases, respectively, in leptin, resistin, GIP, IGF-1, glucose, insulin, and glucose tolerance. Surprisingly, weight cycled mice had no significant difference in lifespan (801±45 days) as compared to LF fed controls (828±74 days), despite being overweight and eating a HF diet for half of their lives. In contrast, the HF fed group experienced a significant decrease in lifespan (544±73days) compared to LF fed controls and cycled mice. CONCLUSIONS: This is the first controlled mouse study to demonstrate the effect of lifelong weight cycling on longevity. The act of repeatedly gaining and losing weight, in itself, did not decrease lifespan and was more beneficial than remaining obese.